The limitations of commercial serological assays for detection of chlamydial infections in Australian livestock. Issue 4 (6th March 2019) - Bommana, Sankhya; Jelocnik, Martina; Borel, Nicole; Marsh, Ian; Carver, Scott; Polkinghorne, Adam
Abstract : Chlamydia pecorum and Chlamydia abortus are related ruminant pathogens endemic to different global regions. Potential co-infections combined with the lack of species-specific serological assays challenge accurate diagnosis. Serological screening revealed low C. abortus seropositivity with the peptide-based ELISA (1/84; 1.2%) in Australian sheep yet moderate seropositivity in a Swiss flock with history of C. abortus -associated abortions (17/63; 26.9%). By whole cell antigen complement fixation tests (CFT) and ELISA, chlamydial seropositivity was significantly higher in all groups, suggesting cross-reactivity between these two chlamydial species and non-specificity of the tests. However, only C. pecorum DNA could be detected by qPCR in Chlamydia seropositive Australian animals screened, suggesting chlamydial seropositivity was due to cross-reactivity with endemic C. pecorum infections . These results suggest ascribing Chlamydia seropositivity to chlamydial species in livestock using whole-cell antigen CFT or ELISA should be treated with caution; and that peptide-based ELISA and qPCR provide greater chlamydial species-specificity.